Executive Succession in Failing Firms - Schwartz, Kenneth B.; Menon, Krishnagopal (Academy of Management Journal, 1985)
Organizations' environmental contexts can influence their strategies and processes in a number of ways. Pfeffer and Salancik (1978) suggested that context can influence executive succession, because uncertainties, interdependencies, and contingencies in organizational environments affect distribution of power and control within organizations and this distribution, in turn, influences selection and replacement of top executives. Corporate chiefs can substantially affect major organizational characteristics, so their replacement can produce organizational change. A number of investigations on executive succession patterns have considered change in top management as a critical determinant of organizations' adaptive behaviors (e.g. Dalton Helmich, 1974; Helmich Hughes, 1982). Outside stakeholders may insist upon top management changes as a condition of their continued support, or managers may consider resignation or early retirement as being in their own best interests (Business Week, 1983). Although companies in financial distress may replace chief executive officers (CEOs) because of incumbent leaders' perceived inadequacies, there may also be a symbolic dimension to CEO change. Pfeffer and Salancik (1978) pointed out that top managers have symbolic roles in organizations and can serve as scapegoats, rewarded when things go well, fired when things go poorly. Replacing CEOs may help to change both internal and external perceptions of companies' images and help restore confidence in their futures. Two recent studies of the association between corporate performance and executive succession (Bibeault, 1982; Schendel, Patton, & Riggs, 1976) have indicated that management changes are a characteristic strategy in turnaround companies. Although external pressures on companies may necessitate replacing top management, such changes alone may not solve all of the problems that face companies in acute financial distress. The present study examines the frequency with which failing companies change CEOs in the years immediately preceding their filing for bankruptcy. This study also looks at patterns of top executive succession in failing companies. Often, firms view selection of insiders as a maintenance or nonadaptive strategy, and believe outside successors will bring about needed radical changes. In studying patterns of executive succession, both Helmich and Brown (1972) and Dalton and Kesner (1983) found substantially greater proportions of insider than outsider replacements. Decision makers may perceive failing companies as needing new management teams with special turnaround skills to handle difficult situations and make crucial policy and strategy decisions. Executives possessing skills not found in existing management can appear more likely to succeed in overhauling operations?more likely, for instance, to be hard-nosed or to act as a hatchet man. The absence of such characteristics among existing management might result in failing companies seeking outside talent to help solve their problems. Dalton and Kesner (1983) cited organizational size as an influence on executive succession patterns. Their argument suggests that large organizations are more likely than small firms to replace top management from inside, because the former have reservoirs of management talent, and also because their managers have more power to resist the imposition of outside chiefs than small firms' managers do.?